The effects of environmental chemicals on renal function - Kataria, Anglina; Trasande, Leonardo; Trachtman, Howard (Nature reviews. Nephrology, 2015)
Key Points Exposure to organic contaminants occurs through normal daily and routine medical procedures, and is ubiquitous among healthy children and adults Exposure to environmental chemicals that can damage the kidney can occur via dietary intake or as a consequence of medical interventions, such as haemodialysis or parenteral nutrition The full impact of persistent exposure to environmental chemicals on renal function has not been addressed in great detail Cross-sectional data from numerous studies worldwide indicate that exposure to organic chemicals can have adverse effects on glomerular filtration rate, albuminuria, blood pressure and serum uric acid concentration Oxidative stress is a contributing factor to the adverse effects of environmental chemicals on cardiorenal function; additional studies are required to clarify the mechanism and long-term effects of environmental chemicals The identification of modifiable risk factors that are associated with declining renal function is required to stem the increasing incidence of chronic kidney disease worldwide. In this Review, Howard Trachtman and colleagues discuss the impact of environmental chemicals on cardiorenal function. They highlight the ubiquity of exposure to environmental chemicals in the general public, the main sources of contamination, and the predominant adverse effects that might affect renal function. The global incidence of chronic kidney disease (CKD) is increasing among individuals of all ages. Despite advances in proteomics, genomics and metabolomics, there remains a lack of safe and effective drugs to reverse or stabilize renal function in patients with glomerular or tubulointerstitial causes of CKD. Consequently, modifiable risk factors that are associated with a progressive decline in kidney function need to be identified. Numerous reports have documented the adverse effects that occur in response to graded exposure to a wide range of environmental chemicals. This Review summarizes the effects of such chemicals on four aspects of cardiorenal function: albuminuria, glomerular filtration rate, blood pressure and serum uric acid concentration. We focus on compounds that individuals are likely to be exposed to as a consequence of normal consumer activities or medical treatment, namely phthalates, bisphenol A, polyfluorinated alkyl acids, dioxins and furans, polycyclic aromatic hydrocarbons and polychlorinated biphenyls. Environmental exposure to these chemicals during everyday life could have adverse consequences on renal function and might contribute to progressive cumulative renal injury over a lifetime. Regulatory efforts should be made to limit individual exposure to environmental chemicals in an attempt to reduce the incidence of cardiorenal disease.